Comparison of Metabolic Alterations in Serum and Milk Whey Between Inactive Ovaries and Estrus Dairy Cows - Zhao, Chang; Bai, Yunlong; Fu, Shixin; Wu, Ling; Xia, Cheng; Xu, Chuang (Frontiers in Veterinary Science, 2021)
Inactive ovaries (IO) affect the estrus cycle and timed artificial insemination (TAI) efficiency in dairy cows during early lactation. The objective of the experiment was to determine metabolic changes in serum and milk whey of dairy cows with IO and estrus. Twenty-eight healthy postpartum Holstein cows in similar age, milk production, and body condition were selected at 30 d postpartum for tracking to 70 d postpartum and estrus performance was recorded through Afi Farm® software. The ovarian status and follicular diameter of dairy cows were examined by an experienced breeder through B-ultrasound and rectal examination. Fourteen normal estrus cows were allocated to control group A and 14 cows with IO to group B, all at 30 to 70 d postpartum. Serum and milk whey in the two groups of cows at 70 d postpartum were used for non-targeted nuclear magnetic resonance (1H-NMR) analysis to measure the different metabolites of cows with IO. In Group B compared with Group A at 70 d postpartum, there was an increase in milk whey of six different metabolites including succinate, creatine phosphate, glycine, myo-inositol, glycolate and orotate and a decrease in milk whey of seven metabolites, including alanine, creatinine, o-phosphorylcholine, lactose, taurine, galactose and glucose-1-phosphate. There was an increase in serum of Group B cows of four differential metabolites, including 3-hydroxybutyrate, acetate, glutamine and glycine and a decrease in serum of nine differential metabolites, including alanine, succinate, citrate, creatinine, o-phosphocholine, glucose, myo-inositol, tyrosine and histidine compared with Group A. Group B cows with IO had decreased glucose metabolism and impaired tricarboxylic acid cycle, increased lipid mobilization and abnormal amino acid metabolism. The study provides a potential prevention strategy for IO in dairy cows in future.